2005
DOI: 10.1158/1078-0432.ccr-1004-0016
|View full text |Cite
|
Sign up to set email alerts
|

Application of High Amplitude Alternating Magnetic Fields for Heat Induction of Nanoparticles Localized in Cancer

Abstract: Objective: Magnetic nanoparticles conjugated to a monoclonal antibody can be i.v. injected to target cancer tissue and will rapidly heat when activated by an external alternating magnetic field (AMF). The result is necrosis of the microenvironment provided the concentration of particles and AMF amplitude are sufficient. High-amplitude AMF causes nonspecific heating in tissues through induced eddy currents, which must be minimized. In this study, application of highamplitude, confined, pulsed AMF to a mouse mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
143
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(146 citation statements)
references
References 17 publications
1
143
1
1
Order By: Relevance
“…Induction heating devices for generating an AMF generally use a ferromagnetic core structure or induction coil structure [4][5][6][7]. The devices employing ferromagnetic core have been used in clinical experiments [6][7][8] but it is difficult for them to further improve the frequency and intensity of the AMF due to the large volume of the core and significant self-heating inside it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction heating devices for generating an AMF generally use a ferromagnetic core structure or induction coil structure [4][5][6][7]. The devices employing ferromagnetic core have been used in clinical experiments [6][7][8] but it is difficult for them to further improve the frequency and intensity of the AMF due to the large volume of the core and significant self-heating inside it.…”
Section: Introductionmentioning
confidence: 99%
“…The devices employing ferromagnetic core have been used in clinical experiments [6][7][8] but it is difficult for them to further improve the frequency and intensity of the AMF due to the large volume of the core and significant self-heating inside it. With smaller volume and less self-heating, the induction coil, which generally based on resonant inverters, was used and researched more and more frequently [5,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…64 Ivkov et al reported the feasibility of applying high-amplitude AMF to treat cancer tissue with embedded magnetic NPs in 39 female BALB/c athymic nude mice and observed no adverse effects in mice exposed to AMF amplitudes of #700 Oe but mice exposed to AMF amplitudes in excess of 950 Oe experienced morbidity and injury. 72 Preclinical studies on various types of cancer using magnetic hyperthermia have been reported to have promising tumor responses in mouse models. These studies have been pursued independently by different research teams for breast, prostate, and brain tumor models.…”
Section: Heating Cancer With Magnetic Npsmentioning
confidence: 99%
“…radius of exposed region [32], can lead to distant painful hot spots that would limit the values of f and H, and thus the heating possibilities. The AMF used here is associated with (H Á f ) values ranging from 10Á10 8 to 13.5Á10 8 A/(mÁs) for 9 mT (7.2 kA/m) and 12 mT (9.6 kA/m), at 141 kHz.…”
mentioning
confidence: 99%
“…(H Á f ) values higher than 20Á10 8 A/m/s have been used in and ex vivo [37,38]. Pulses of very high amplitude have been experimentally used in mice [32].…”
mentioning
confidence: 99%